InterRAI assessments: opportunities to recognise need for and implementation of palliative care interventions in the last year of life?. (9th August 2020) - Robinson, Jackie; Frey, Rosemary; Boyd, Michal; McLeod, Heather; Meehan, Brigette; Gott, Merryn
Abstract: Objectives: To explore how interRAI assessments could be used to identify opportunities to integrate palliative care into a plan of care. Methods: A population‐based, cross‐sectional design using unique identifiers to link deaths with a national interRAI database. Data were analysed using logistic regression models and chi‐square tests. Results: A total of 4869 people died over a 12‐month period in one district health board area; 50.9% (n = 2478) received one or more interRAI assessments in the year before death. Diagnosis impacted on the type and timing of interRAI assessments and the recognition of end‐stage disease. Conclusion: People in the last year of life experience frequent interRAI assessments. There are opportunities to identify people who might benefit from a palliative care approach. Future research is needed to understand how interRAI assessors can be supported in the application of assessment items related to palliative care.